Use of Glycoprotein IIb-IIIa Inhibitor for a Thromboembolic Complication during Guglielmi Detachable Coil Treatment of an Acutely Ruptured Aneurysm - Ng, Perry P.; Phatouros, Constantine C.; Khangure, Makhan S. (American Journal of Neuroradiology, 2001)
Summary: Thrombotic occlusion of the anterior communicating and right anterior cerebral arteries occurred during embolization of an acutely ruptured aneurysm of the anterior communicating artery. Traditional management, including superselective infusion of a fibrinolytic agent, was unsuccessful in reestablishing normal vessel patency. Therefore, an intravenous dose of abciximab was administered. Serial angiography showed that normal vessel patency was reestablished within 10 min. There were no adverse events related to abciximab administration, and the patient recovered from the procedure without neurologic deficit.